Knowledge and Attitudes Towards Pregnancy in Females with Inflammatory Bowel Disease: An International, Multi-centre Study. (11th March 2020) - Laube, Robyn; Yau, Yunki; Selinger, Christian P; Seow, Cynthia H; Thomas, Amanda; Wei Chuah, Sai; Hilmi, Ida; Mao, Ren; Ong, David; Ng, Siew C; Chen Wei, Shu; Banerjee, Rupa; et al.
Abstract: Background and Aims: Poor knowledge of inflammatory bowel disease [IBD] in pregnancy underlies unwarranted voluntary childlessness [VC], and risks poorer obstetric outcomes and adverse fetal outcomes. IBD is increasing worldwide but education on IBD issues might be heterogeneous based on cultural differences and variations in models of care. Methods: Consecutive female IBD subjects aged 18–45 years were prospectively recruited from two dedicated IBD-pregnancy clinics, two multidisciplinary IBD clinics and nine general gastroenterology clinics. Subjects completed the validated CCPKnow [score 0–17] with questions on demographics, medical history and pregnancy knowledge. The primary outcome was knowledge per clinic-type and per geographical region. Results: Surveys were completed by 717 subjects from 13 hospitals across ten countries. Dedicated IBD-pregnancy clinics had the highest knowledge, followed by multidisciplinary IBD clinics then general IBD clinics (median CCPKnow 10.0 [IQR: 8.0–11.0], 8.0 [IQR: 5.0–10.5] and 4.0 [IQR:2.0–6.0]; p < 0.001). Median CCPKnow scores in Western, Asian and Middle Eastern clinics were 9.0, 5.0 and 3.0 respectively [ p < 0.001]. Dedicated IBD-pregnancy clinics, IBD support organization membership, childbearing after IBD diagnosis and employment independently predicted greater knowledge. Patient perception of disease severity [ r = − 0 .18, p < 0.01] and consideration of VC [ r = − 0 .89, p = 0.031] negatively correlated with CCPKnow score. The overall VC rate was 15.0% [95% CI: 12.2–18.2]. VC subjects had significantly lower pregnancy-specific IBD knowledge than non-VC subjects (median CCPKnow 4.0 [IQR: 2.0–6.0] and 6.0 [IQR: 3.0–9.0] respectively; p < 0.001). Pregnancy-specific IBD knowledge and dedicated IBD-pregnancy clinic attendance were significant negative predictors of VC. Conclusions: In this large international study we identified predictors of pregnancy-specific IBD knowledge. Dedicated IBD-pregnancy clinics had the greatest IBD-related pregnancy knowledge and lowest VC rates, reflecting the benefits of pre-conception counselling.